Modulation of MicroRNAs by Chemical Carcinogens and Anticancer Drugs in Human Cancer: Potential Inkling to Therapeutic Advantage - Haldar, Subrata (2011)
The disorder of microRNAs (miRNAs) often referred as ‘micromanagers of gene expression’ has been implicated with a vast array of neoplasmthe discovery establishes an important connection with the etiology, diagnosis and potential therapy of human cancer. Indeed, the wide range of profiling studies enabled to create miRNA signatures of solid tumors as well as cancers of blood origin. MiRNAs have been observed to play a significant role in the regulation of gene expression-a critical aspect of many biological processes, including cell development, differentiation, apoptosis and proliferation. The differential expression levels of miRNAs in tumors and their normal counterpart have enabled scientists to designate their roles as oncomir or tumor suppressor. Interestingly, the diminishment of oncogenic or enhanced levels of tumor suppressor miRNAs (antagomirs) have been reported to modulate the sensitivity of cancer cells to anticancer agents. To the other end, carcinogenic chemicals either possess the ability of silencing beneficial tumor suppressive miRNAs or maintain the augmented levels of their oncogenic counterpart. In this article we provide a comprehensive overview on the modulation of these “micromanaging oligos” by cancer causing as well as cancer preventing agents.